Peripheral refraction in myopic patients after Orthokeratology - Queirós, A. (2010)
Purpose: The purpose of this study was to characterize the central and peripheral refraction across the horizontal meridian of the visual field before and after myopic corneal refractive therapy (CRT) with contact lenses. Methods: Twenty-eight right eyes (mean age±SD = 24.6±6.3 years) were fitted with Paragon CRT contact lenses to treat myopia between -0.88 and -5.25D of spherical equivalent. Along with a complete set of examination procedures to assess suitability for treatment, the central and peripheral refraction was measured along the horizontal meridian up to 35º of eccentricity in the nasal and temporal retinal area in 5º steps. Results: Baseline central average spherical equivalent (M) measured by subjective refraction changed from -1.95±1.27D to -0.38±0.67D. Changes in M component ranged between 1.42±0.89D at center to 0.43±0.88D at 20º in the temporal retina (p<0.002). At 25º to both sides of the central refraction measurement, peripheral refraction after treatment was not statistically different from baseline values (p>0.351). Beyond the 25º limit, M component changed in the myopic direction up to -1.11±0.88D at 35º in temporal retina (p<0.001). Treatment induced was symmetric between nasal and temporal visual field along the horizontal meridian (p>0.05 for all eccentricities). Furthermore, the degree of myopic increase in spherical equivalent for 30º (r2=0.573, p<0.001) and 35º (r2=0.645, p<0.001) eccentric refraction was highly correlated with axial spherical equivalent at baseline. Conclusions: CRT inverts the pattern of peripheral refraction in spherical equivalent refraction creating a treatment area of myopic reduction within the central 25º of visual field, and a myopic shift beyond the 25º. In peripheral refraction for 30º and 35º, the amount of myopia induced in terms of spherical equivalent has an almost 1:1 relationship with the amount of baseline spherical equivalent refraction to be corrected.